Detecção de parafina por instrumentação ultrassônica - Nabeyama, Guilherme Natsutaro Descrovi (2015)
An obstruction in the oil pipelines’ inner walls of transport and production due to hydrocarbon deposition is a serious problem that can cause operational risks, equipment losses and lead to losses to the industry. This work aims to conduct experiments using ultrasonic waves, to detect paraffin deposits on steel surfaces, focusing in the estimation of the thickness of these accumulations. The tests were conducted in a test rig where specimens with different thicknesses of steel and paraffin deposits were measured. The experimental results showed that due to the difference between the acoustic properties of the steel and paraffin the use of ultrasound, for detecting paraffin deposits, becomes a very complex task. Measuring accurately is dependent on the medium that will interface with the wax, which must have certain characteristics for the acoustic impedance coupling with the deposit, allowing a greater reflection of the ultrasound signal. The echo suppression technique used to detect the deposits proved to be quite satisfactory, providing a response value with uncertainty of less than 0.32mm.